Bi(III) Complexes Containing Dithiocarbamate Ligands: Synthesis, Structure Elucidation by X‐ray Diffraction, Solid‐State 13C/15N NMR, and DFT Calculations. Issue 29 (4th August 2020) - Gowda, Vasantha; Sarma, Bipul; Larsson, Anna‐Carin; Lantto, Perttu; Antzutkin, Oleg. N.
Abstract: We report on syntheses, characterisation by nuclear magnetic resonance (NMR) spectroscopy, X‐ray diffraction (XRD) measurements, and density functional theory (DFT) calculations of electronic/molecular structure and NMR chemical shifts of complexes of Bi(III), having the molecular formulae: [BiS2 CN(C2 H5 )2 )3 ] (1 ), [BiS2 CN(C2 H5 )2 )2 (C12 H8 N2 )NO3 )] (2 ), and [Bi2 S2 CN(CH2 )5 6 H2 O] (3 ). The powder XRD patterns of complexes (1 ) and (2 ) resembled the corresponding calculated powder XRD patterns for previously reported single crystal structures. Single crystal XRD structure of complex (3 ), reported in this work, adopted an orthorhombic system with a space group Pbca with a =10.9956(3) Å, b =27.7733(8) Å, c =35.1229(10) Å and α = β = γ =90°. The experimental solid‐state 13 C/ 15 N NMR data of the complexes (1 )‐(3 ) were in accord with their X‐ray single crystal structures. The unit cell of the complex (3 ) shows a weak supramolecular Bi ⋯ S interaction leading to the formation of a non‐centrosymmetric binuclear molecule [Bi2 S2 CN(CH2 )5 6 H2 O], which displays structural inequivalence in both 13 C/ 15 N NMR, and XRD data. Assignments of resonance lines in solid‐state 13 C/ 15 N NMR spectra of complexes (1 )‐(3 ) were assisted by chemical shift calculations using periodic DFT methods. The findings of the present multidisciplinary approach will contribute in designing molecular models and further understanding of the structures and properties of (diamagnetic) metal complexes, including heavy metal ones. Abstract : An NMR crystallography method is presented for the structure elucidation of homo‐ and heteroleptic Bi(III)‐dithiocarbamate complexes using 13 C/ 15 N NMR chemical shifts measured by solid‐state NMR spectroscopy and calculated by periodic density functional theory. The findings of the present multidisciplinary approach will contribute to the structural refinement of diamagnetic complexes, especially, involving heavy metal ones.